Treatment With Lisinopril Prevents the Early Progression of Glomerular Injury in Obese Dahl Salt-Sensitive Rats Independent of Lowering Arterial Pressure - Brown, Andrea K.; Nichols, Alyssa; Coley, Chantell A.; Ekperikpe, Ubong S.; McPherson, Kasi C.; Shields, Corbin A.; Poudel, Bibek; Cornelius, Denise C.; Williams, Jan M. (Frontiers in Physiology, 2021)
Recently, we reported that obese Dahl salt-sensitive leptin receptor mutant (SSLepRmutant) rats develop glomerular injury and progressive proteinuria prior to puberty. Moreover, this early progression of proteinuria was associated with elevations in GFR. Therefore, the current study examined whether treatment with lisinopril to reduce GFR slows the early progression of proteinuria in SSLepRmutant rats prior to puberty. Experiments were performed on 4-week-old SS and SSLepRmutant rats that were either treated with vehicle or lisinopril (20 mg/kg/day, drinking water) for 4 weeks. We did not observe any differences in MAP between SS and SSLepRmutant rats treated with vehicle (148 ± 5 vs. 163 ± 6 mmHg, respectively). Interestingly, chronic treatment with lisinopril markedly reduced MAP in SS rats (111 ± 3 mmHg) but had no effect on MAP in SSLepRmutant rats (155 ± 4 mmHg). Treatment with lisinopril significantly reduced proteinuria in SS and SSLepRmutant rats compared to their vehicle counterparts (19 ± 5 and 258 ± 34 vs. 71 ± 12 and 498 ± 66 mg/day, respectively). Additionally, nephrin excretion was significantly elevated in SSLepRmutant rats versus SS rats, and lisinopril reduced nephrin excretion in both strains. GFR was significantly elevated in SSLepRmutant rats compared to SS rats, and lisinopril treatment reduced GFR in SSLepRmutant rats by 30%. The kidneys from SSLepRmutant rats displayed glomerular injury with increased mesangial expansion and renal inflammation versus SS rats. Chronic treatment with lisinopril significantly decreased glomerular injury and renal inflammation in the SSLepRmutant rats. Overall, these data indicate that inhibiting renal hyperfiltration associated with obesity is beneficial in slowing the early development of glomerular injury and renal inflammation.